Employment Effects of Innovation at the Firm Level - Stefan Lachenmaier; Horst Rottmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2006)
This paper analyzes empirically the effects of innovation on employment at the firm levelusing a uniquely long panel dataset of German manufacturing firms. The overall effect ofinnovations on employment often remains unclear in theoretical contributions due to reverseeffects. We distinguish between product and process innovations and introduce in additiondifferent innovation categories. We find clearly positive effects for product and processinnovations on employment growth with the effects for process innovations being slightlyhigher. The effects are stronger in small firms and differ between firms in former West andEast Germany.
Keywords: J23; L60; O30; 330; innovation; labour demand; employment; firm size; panel data